Meningkatkan Pengetahuan Dan Keterampilan Petani Dalam Pembuatan Pupuk Organik Bokashi Di Gereja Marturia Oesapa Selatan Kota Kupang - Nur Aini Bunyani; Frengky Neolaka; Abdonia W. Finmeta; Eka C.G. Kerihi; Charizal M.A. Manu; Maya F. Roman; Nardi M. Leo (Jurnal Pengabdian Kepada Masyarakat, 2023)
The community at the Marturia Oesapa Selatan Church has a population of 600 people and 26 of them work as farmers, retirees and traders. Based on observations and surveys conducted in February 2023, the problems encountered are still using inorganic fertilizers for agriculture, fertilizing ornamental plants and fertilizing horticultural plants in the yard of the house for more practical reasons, but the community does not yet know the impact of using inorganic fertilizers. The purpose of holding this PKM activity is to increase public understanding of the negative impacts of using inorganic fertilizers, increase understanding of the benefits of using organic fertilizers and provide training on how to process household waste into organic fertilizer. This community service took place at the Marturia Oesapa Selatan Church in Kupang City on Wednesday 1 March 2023 with 26 participants. The first stage is to conduct field observations and coordinate with the Head of the Marturia Oesapa Selatan Church regarding the cooperation agreement and the place and time of implementation. The second stage is preparing training materials. The third stage is the implementation of training on processing household waste into organic fertilizer. As a result of PKM activities, participants understand the importance of organic fertilizer for plantations, ornamental plants, horticultural crops and utilization of natural resources around them to be processed into bokashi organic fertilizer. Participants also have the skills to make bokashi organic fertilizer after participating in this activity, judging from the success of carrying out the work steps given during counseling and technical instructions in making organic fertilizer. Keywords: Household waste, bokashi organic fertilizer